Assessment of Ocimum canum Sims. essential oil as phyto-preservative against fungal deterioration of vasicine of stored herbal raw materials of Justicia adhatoda L. - Kumar, Ashok; Kumari, Sanyogita; Dubey, Nawal Kishore (Journal of Postharvest Technology, 2023)
The stored herbal raw materials of Justicia adhatoda were found contaminated with various storage fungi in which Aspergillus flavus exhibited the maximum relative density (26.41%). The chemical profile of Ocimum canum essential oil (OcEO) showed 31 considerable peaks. E-Citral (30.31%) was found as major component followed by Z-Citral (18.23%) and Epoxy ocimene (5.77%). OcEO exhibited broad spectrum fungitoxicity and MIC against A. flavus LHPJA-09 was recorded at 0.5 mg/ml while aflatoxin B1 production was completely checked at 0.3 mg/ml. The detectable reduction in ergosterol amount as well as increased leakage of cellular cations (K+, Ca2+ and Mg2+) specify plasma membrane as the possible target site of antifungal action. OcEO also exhibited significant antioxidant potential with IC50 value (4.3 μg/ml) comparable to synthetic antioxidants would be helpful to minimize lipid peroxidation. The high performance thin layer chromatography (HPTLC) analysis of fumigated stored raw materials reveals that OcEO was found efficacious to control the degradation of medicinal component, vasicine of J. adhatoda. The LD50 of OcEO against mice was recorded as 6050.36 mg/kg body weight indicating its non mammalian toxicity. Hence, OcEO exhibited special virtues possessing antifungal, antiaflatoxigenic, antioxidant and non-mammalian toxicity strengthening its safe exploitation as green preservative.